Cover Image, Volume 41, Issue 9. (14th June 2017) - Liu, Zhen; Qu, Na; Shi, Hongda
Abstract : The cover image, by Zhen Liu et al., is based on the Research Article Experimental study on hydrodynamic performance of a wave energy converter within multi‐heaving‐buoys, DOI10.1002/er.3725 . Financial support was provided by the National Natural Science Foundation of China (41376100), "863" project (2012AA0526), Shandong Natural Science Funds for Distinguished Young Scholar (JQ201314) and Innovation Project (2014ZZCX06105), the Fundamental Research Funds for the Central Universities (201564005) and the Program of Introducing Talents of Discipline to Universities (111 Project, B14028).